Melatonin and its kynurenin-like oxidation products affect the microbicidal activity of neutrophils - Silva, S. O.; Carvalho, SRQ; Ximenes, Valdecir Farias [UNESP]; Okada, S. S.; Campa, A. (Elsevier B.V., 2006)
Activated phagocytes oxidize the hormone melatonin to N-1-acethyl-N-2-formyl-5-methoxykynuramine (AFMK) in a superoxide anion- and myeloperoxidase-dependent reaction. We examined the effect of melatonin, AFMK and its deformylated-product N-acetyl-5-methoxykynuramine (AMK) on the phagocytosis, the microbicidal activity and the production of hypochlorous acid by neutrophils. Neither neutrophil and bacteria viability nor phagocytosis were affected by melatonin, AFMK or AMK. However these compounds affected the killing of Staphylococcus aureus. After 60 min of incubation, the percentage of viable bacteria inside the neutrophil increased to 76% in the presence of 1 mM of melatonin, 34% in the presence of AFMK and 73% in the presence of AMK. The sole inhibition of HOCl formation, expected in the presence of myeloperoxidase substrates, was not sufficient to explain the inhibition of the killing activity. Melatonin caused an almost complete inhibition of HOCl formation at concentrations of up to 0.05 mM. Although less effective, AMK also inhibited the formation of HOCl However, AFMK had no effect on the production of HOCl These findings corroborate the present view that the killing activity of neutrophils is a complex phenomenon, which involves more than just the production of reactive oxygen species. Furthermore, the action of melatonin and its oxidation products include additional activities beyond their antioxidant property. The impairment of the neutrophils' microbicidal activity caused by melatonin and its oxidation products may have important clinical implications, especially in those cases in which melatonin is pharmacologically administered in patients with infections. (c) 2005 Elsevier SAS. All rights reserved.
Keywords: melatonin; myeloperoxidase; neutrophil; killing activity; hypochlorous acid; phagocytosis